Absenteeism and Scholastic Abandonment: A Singular Situation of the Educative Exclusion - Sara Redondo Duarte; Enrique Navarro Asencio (Universidad Autónoma de Madrid, 2018)
This paper is inside the frame of an educational innovation project called "Other world is possible, other world is necessary". The project was implemented in a high school in Madrid and it deals with values education. All the educational community were involved in the project. The aim of this survey was to discover those factors that induce teachers to participate in this kind of project. Two instruments were used in order to collect the information: a questionnaire applied to all the teachers involved in the project and an interview for certain teachers belonging to three Teaching Departments and with different levels of involvement in the project. The frame of reference of this study uses a methodology called "Sistematización".